2022
DOI: 10.7759/cureus.29709
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular Actinomycosis: Behind the Curtains of Appendicitis

Abstract: Actinomycosis is a rare, indolent, and multisystemic infection caused by Actinomyces, commensal bacteria of the oral and intestinal flora. It usually occurs due to tissue disruption. It affects the abdominal region in 20% of cases, and the most common presentation is a perforated appendix. Symptoms are nonspecific, which makes differential diagnosis a challenge.We present the case of a healthy, nine-year-old boy of African ancestry with a five-month history of recurrent intermittent abdominal pain in the periu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…A retrospective study of 1627 appendectomy specimens showed only one case (0.06%) of actinomycosis, 1 whereas the evaluation of 3602 appendicectomy specimens in another study showed only a case of actinomycosis (0.02%). 2 There are few cases reported for actinomycosis of the appendix [5][6][7][8][9][10][11] ; however, this study seems to be the first of its kind to be reported from the country.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…A retrospective study of 1627 appendectomy specimens showed only one case (0.06%) of actinomycosis, 1 whereas the evaluation of 3602 appendicectomy specimens in another study showed only a case of actinomycosis (0.02%). 2 There are few cases reported for actinomycosis of the appendix [5][6][7][8][9][10][11] ; however, this study seems to be the first of its kind to be reported from the country.…”
Section: Discussionmentioning
confidence: 90%
“…Actinomycosis is a rare infectious disease caused by actinomyces species, which is a gram‐positive anaerobic bacterium 3,4 . Despite the clear statistical data, an incidence of 0.3–1 incident per year per 100,000 people has been estimated 5 . It occurs as a commensal in the oral cavity, gastrointestinal tract, and female genital tract, and becomes pathogenic when the mucosal barrier is breached 3,4,7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations